2005
DOI: 10.1128/jcm.43.8.3755-3759.2005
|View full text |Cite
|
Sign up to set email alerts
|

Ability of the Vector Tick Boophilus microplus To Acquire and Transmit Babesia equi following Feeding on Chronically Infected Horses with Low-Level Parasitemia

Abstract: The protozoan parasite Babesia equi replicates within erythrocytes. During the acute phase of infection, B. equi can reach high levels of parasitemia, resulting in a hemolytic crisis. Horses that recover from the acute phase of the disease remain chronically infected. Subsequent transmission is dependent upon the ability of vector ticks to acquire B. equi and, following development and replication, establishment of B. equi in the salivary glands. Although restriction of the movement of chronically infected hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(94 citation statements)
references
References 24 publications
4
75
0
3
Order By: Relevance
“…microplus was susceptible to infection by T. equi and was able to transmit it to horses. This finding was later confirmed by other workers (STILLER et al, 2002;UETI et al, 2005;2008). Cattle are the primary host for R.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…microplus was susceptible to infection by T. equi and was able to transmit it to horses. This finding was later confirmed by other workers (STILLER et al, 2002;UETI et al, 2005;2008). Cattle are the primary host for R.…”
Section: Discussionsupporting
confidence: 80%
“…Studies have shown that three major tick species infest horses in Brazil: Dermacentor nitens (= Anocentor nitens), Amblyomma cajennense, and Rhipicephalus (Boophilus) microplus (FALCE, 1986;BARBOSA et al, 1995;HEUCHERT et al, 1999;LABRUNA et al, 2001;COSTA PEREIRA et al, 2005 (GUIMARÃES et al, 1998;STILLER et al, 2002;UETI et al, 2005;2008). In fact, T. equi-infected horses have been reported in areas where R.…”
Section: Introductionmentioning
confidence: 99%
“…Hoje, no Brasil, a importância de R. microplus ultrapassa os interesses da pecuária bovina e recai também sobre a criação equina, sobremaneira, pela transmissão de T. equi (UETI et al, 2005), um hemoparasita que afeta o desempenho de equinos, seja de trabalho ou esporte, bem como causa restrições no comércio internacional de equinos infectados (FRIEDHOFF et al, 1990).…”
Section: Resultsunclassified
“…T. parva is acquired by immature ticks during blood feeding, and transmission of T. parva is strictly trans-stadial as the parasite is transmitted only by the nymphal and adult stages after acquiring infections during feeding as larvae or nymphs, respectively. In tick-borne hemoprotozoan parasite infections, the level of parasitemia in the reservoir hosts at the time of tick feeding is critical for efficient acquisition of the pathogens by the ticks (Eriks et al, 1993;Ueti et al, 2005). Interestingly, Ueti et al (2005) have demonstrated the ability of the vector tick Boophilus microplus to acquire and transmit Babesia equi following feeding on chronically infected horses with low-level parasitemia.…”
Section: Introductionmentioning
confidence: 99%
“…In tick-borne hemoprotozoan parasite infections, the level of parasitemia in the reservoir hosts at the time of tick feeding is critical for efficient acquisition of the pathogens by the ticks (Eriks et al, 1993;Ueti et al, 2005). Interestingly, Ueti et al (2005) have demonstrated the ability of the vector tick Boophilus microplus to acquire and transmit Babesia equi following feeding on chronically infected horses with low-level parasitemia. Ticks (7.1-50%) that acquired B. equi from chronically infected horses, 4 as well as those (22%) fed during the acute phase of infection, successfully transmitted the parasite to naive horses.…”
Section: Introductionmentioning
confidence: 99%